2012
DOI: 10.31729/jnma.371
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure in Inhabitants of High Altitude of Western Nepal

Abstract: Introduction: Studies conducted amongst the inhabitants of high altitude suggested that systolic and diastolic blood pressures are lower in the high than in low altitude population. So a study was designed to look at the blood pressure values among permanent residents of high altitudes of rural Western Nepal. Methods: This is a descriptive cross sectional study conducted at two different altitudes (2670 and 2950 meters) of Humla District, Nepal, looking at the blood pressure values among the permanent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
2
16
2
Order By: Relevance
“…The prevalence of HT (or those on anti-hypertensive medication) in participants in the present study is higher than in other studies carried out in HA populations in Nepal using a similar definition [26][27][28] .…”
Section: Discussioncontrasting
confidence: 84%
“…The prevalence of HT (or those on anti-hypertensive medication) in participants in the present study is higher than in other studies carried out in HA populations in Nepal using a similar definition [26][27][28] .…”
Section: Discussioncontrasting
confidence: 84%
“…Contradicting results have been found in studies of the relationship between BP and chronic hypoxic-hypobaric conditions in individuals living at high altitude. One study performed in Nepalese individuals living at high altitude in a rural location found a lower prevalence of hypertension, suggesting that BP decreased with the increase in altitude [5]. However, previous research performed by our group showed that BP levels were significantly higher in children living at 3750 m compared with children from a community of a similar background but living at a lower altitude (1400 m) [6].…”
Section: Introductioncontrasting
confidence: 51%
“…For example, a systematic review analysed different cross-sectional surveys from Tibet and suggested a positive correlation between altitude and the prevalence of hypertension 22. Conversely, lower rates of hypertension have been observed in individuals from high-altitude rural areas of Nepal 23. There is evidence that blood pressure does not vary in response to short-term hypoxic exposure;24 and increased blood pressure during altitude adaptation is explained by sympathetic nervous system activation 25.…”
Section: Discussionmentioning
confidence: 99%